2017
DOI: 10.1111/mve.12227
|View full text |Cite
|
Sign up to set email alerts
|

Differences in competitive ability for the occupancy of shelters in triatomines

Abstract: Triatomines (Hemiptera: Reduviidae: Triatominae) are nocturnal blood-sucking insects. During daylight hours they remain in an akinetic state inside their shelters, whereas at dusk they become active and move outside. When they are outside their shelters during the photophase, triatomines are vulnerable to diurnal predators and the period just before dawn is critical to their survival. This work analyses the existence of competitive interactions involved in the occupancy of shelters by triatomines. Behavioural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…In the first part of this work, a mixed group of fed and unfed nymphs showed an even coexistence inside all the shelters available, although previous works show that the physiological feeding status of a triatomine insect directly affects its mobility, locomotor activity, competing capacities for shelters, and host-seeking behaviour (Lazzari, 1992;Takano-Lee & Edman, 2001;Zacharias et al, 2017). Therefore, it is expected to see shelters in nature occupied by conspecifics with different degrees of feeding in T. infestans and R. prolixus.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In the first part of this work, a mixed group of fed and unfed nymphs showed an even coexistence inside all the shelters available, although previous works show that the physiological feeding status of a triatomine insect directly affects its mobility, locomotor activity, competing capacities for shelters, and host-seeking behaviour (Lazzari, 1992;Takano-Lee & Edman, 2001;Zacharias et al, 2017). Therefore, it is expected to see shelters in nature occupied by conspecifics with different degrees of feeding in T. infestans and R. prolixus.…”
Section: Discussionmentioning
confidence: 83%
“…However, nutritional status has also a clear effect on this rhythmicity, since fasted T. infestans showed an increased frequency of entry and exit from their shelters . Similarly, Zacharias et al (2017) demonstrated that occupancy levels of shelters are higher in fed than in fasted nymphs of the same species. In R. prolixus, Takano-Lee and Edman (2001) described that fasted nymphs sought more shelter than recently fed ones.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Specimens of the four studied cohorts required a low number of blood meals to molt, which suggests a higher fitness. This would be an advantage because a triatomine may be at risk each time it leaves the harborage to locate a host (Zacharias et al ). The accumulative mortality of M. bassolsae was noticeably higher in moltings from the 1 st to the 2 nd instar, from the 5 th instar to the adult stage, and in the total percentage, in comparison to the other three studied cohorts.…”
Section: Discussionmentioning
confidence: 99%